Avaliação do desempenho ambiental da produção canavieira com colheita mecanizada: contribuição à implantação de um sistema simplificado de gestão ambiental da propriedade - Gonçalves, Juliana de Fátima [UNESP] (Universidade Estadual Paulista (Unesp), 2008)
The consuming of the natural resources in the agricultural sector does not represent only one external factor of the productive process, but also it implies in a bigger cost for the production, justified for this environmental degradation. In view of the necessity of evaluating the sustainment of the agricultural businesses, the use of performance indicators if makes of extreme importance. The measurement of the support through environmentalindicators is one of the most accepted forms of performing the evaluation of one given agricultural activity. In this context, the Base System for Eco-certification of Agricultural Businesses (Eco-cert Rural) developed by the Embrapa Environment at Jaguariúna/SP, has for purpose to present a method of evaluation of the agricultural businesses, not only of the point of view of the ecological performance, as well as considering the social, economic and organizational aspects. Through the analysis of the performance of the activity and the regularization of the disconformities found, it makes possible the eco-certification of the activities in the varied existing protocols, offering technologies designed to the sustainable development of the agricultural businesses. Using Eco-cert.Rural, this work evaluated the contribution of the use of mechanized harvest in sugar cane handling, front to the traditional system of manual harvest, using the fire. In the Sugar Cane Activity General Performance Index, Agrícola Rio Claro scored 2,08 of a maximum of 15. Amongst all the indicators, those wich reached performance worse had been related to the Use of Energy and the Income, by increasing fossil fuel consumptiom, and implying income concentration due to resignations of rural workers. However, the improvements on the environment quality by supressing manual harvest through fire are very significant. Beyond the great reduction in...(Complete abstract click electronic access below)

O desgaste dos recursos naturais no setor agrícola não representa apenas uma externalidade do processo produtivo, mas também implica num maior custo para a produção, justificado por esta degradação ambiental. Tendo em vista a necessidade de mensurar a sustentabilidade das atividades rurais, a criação de indicadores de desempenho agrícola se faz de extrema importância. A realização de medidas de sustentabilidade através de indicadores ambientais é uma das formas mais aceitas de se realizar a avaliação de desempenho de uma dada atividade agrícola. Neste contexto, o Sistema Base para Eco-certificação de Atividades Rurais (Eco-cert.Rural) desenvolvido pela Embrapa Meio Ambiente em Jaguariúna/SP, tem por finalidade apresentar um método de avaliação das atividades rurais não apenas do ponto de vista do desempenho ecológico como também considerando os aspectos social, econômico e organizacional. Através da análise do desempenho da atividade e a regularização das inconformidades encontradas, viabiliza a eco-certificação das atividades nos variados protocolos existentes, oferecendo tecnologias voltadas ao desenvolvimento sustentável das atividades rurais. Utilizando-se da Eco-certificação, este trabalho avaliou a contribuição da introdução da colheita mecanizada no cultivo de cana-de-açúcar para a sustentabilidade desta cadeia produtiva. O Índice Geral de Desempenho da Atividade Canavieira da propriedade Agrícola Rio Claro alcançou valor igual a 2,08 de um máximo de 15. Dentre todos os indicadores, os que alcançaram pior desempenho foram aqueles relacionados ao Uso de Energia e a Renda, devido ao aumento no uso de combustíveis fósseis e à maior concentração de renda, gerada pela demissão de grande parte dos rurícolas, respectivamente. Entretanto, as melhorias da qualidade ambiental pela eliminação das...(Resumo completo, clicar acesso eletrônico abaixo)
Keywords: Ecologia; Álcool; Cana-de-açúcar; Etanol; Gestão ambiental; Territorial ambient - management; Agricultural businesses